Penggunaan Gadget terhadap Prestasi Akademik Mahasiswa Keperawatan Tingkat I (Journal of Telenursing (JOTING), 2025)
This study aims to determine the relationship between gadget use and academic achievement of first-year nursing students at Universities Advent Indonesia. The method used is quantitative descriptive with a correlation approach. The results showed that most students (72.1%) use gadgets with moderate intensity, with an average score of 62.93. However, 20.9% of students are included in the high usage category, which has the potential to cause negative impacts such as impaired concentration and health. Student academic achievement, measured by GPA, showed an average of 3.34 with a distribution of 34.9% in the "good" category, 22.1% "very good", 18.6% "exceptional". However, 20.9% of students are still in the "poor" category, indicating the need for intervention to improve achievement. Statistical analysis (Spearman's rho) showed no significant relationship between gadget use and GPA (correlation coefficient -0.079, p-value 0.468> 0.05). Conclusion, there is no significant relationship between gadget use and academic achievement of first-year nursing students at Universities Advent Indonesia.  Keywords: Gadgets, Nursing Students, Academic Achievement.